IMPLEMENTASI PROGRAM GERAKAN LITERASI SEKOLAH DALAM MENUMBUHKAN MINAT BACA SISWA DI SMP NEGERI 4 SAMBAS - Yoga Yoga; Sabiqul Huda, Mauizatul Hasanah (ADISAM PUBLISHER, 2025)
This study uses a qualitative approach and the type of research used is Phenomenology. Data collection techniques used are observation, interviews, and documentation. Then the data analysis techniques used in this study are data reduction, data display, data presentation and drawing conclusions. While the technique of checking the validity of research data uses: triangulation and member check. The results of the study show that: (1) the planning of the school literacy movement program in fostering students' interest in reading at SMP Negeri 4 Sambas in this planning includes: (1) The basis in the form of Decree Number: 421/04/SMPN4-SBS/VII/2023 concerning the formation of the school literacy movement team, (2) The goal is to build student awareness and foster students' interest in reading, (3) The target is to make students aware of the importance of reading, (4) Teaching staff, namely the principal, teachers, staff and school committee, (5) School finances budget RKAS (School Activity and Budget Plan) through BOS funds, (6) The organizational structure includes the person in charge, chairman, secretary, material quality aligner, order quality aligner, material collector and reference sources and program implementation, (7) Literacy modules are used as reading materials during the process of the school literacy movement program. (2) Implementation of the school literacy movement program in fostering students' interest in reading at SMP Negeri 4 Sambas. In this implementation, there are three stages, namely the habituation stage, the development stage and the learning stage, and (3) Supporting and inhibiting factors for the implementation of the school literacy movement program in fostering students' interest in reading at SMP Negeri 4 Sambas. In the supporting factors, there is support from the government, the existence of human resources such as teachers and principals and parents, support for adequate facilities and infrastructure, and inhibiting factors are internal factors, namely the lack of student awareness of the importance of reading, the lack of student interest in reading and students still tend to be lazy in terms of reading and external factors, namely such as bad social circles and the influence of gadgets